Considering Tobler's first law of geography in a tourism context. (October 2017) - Joo, Dongoh; Woosnam, Kyle M.; Shafer, C. Scott; Scott, David; An, Soyoung
Abstract: Despite potential benefits from applying Tobler's law in a tourism context, the law has been used sparingly within the tourism literature. This study seeks to expand the use of Tobler's law in tourism research by examining the relationship between tourists' distance travelled to a destination and the perceived degree of emotional closeness such visitors have with community residents. In doing so, visitor data from three uniquely distinct Texas destinations were analyzed. Results suggest that visitors to the destinations not only differed in their average travel distances, but also the perceived levels of emotional solidarity with residents. Results supported Tobler's law in a tourism context, whereby results indicated that the further an individual travelled to a destination, the less they agreed with feeling close to destination residents. Implications and future research direction opportunities are offered at the close of the work. Highlights: Significant difference in visitor's travel distance existed among the destinations. Visitors also differed in their perceived emotional solidarity with residents. An inverse relationship between travel distance and emotional solidarity was found. A compelling argument in support of Tobler's law within a tourism context is made.